Correlative Studies on Sintering of Ni/BaTiO3 Multilayers Using X‐ray Computed Nanotomography and FIB‐SEM Nanotomograhy. Issue 4 (7th January 2015) - Yan, Zilin; Guillon, Olivier; Martin, Christophe L.; Wang, Steve; Lee, Chul‐Seung; Charlot, Frederic; Bouvard, Didier; Randall, Clive Alan
<x xml:space="preserve">Abstract</x> Synchrotron X‐ray computed nanotomography (nCT) and Focused Ion Beam–Scanning Electron Microscope nanotomography (FIB‐nT) were used to characterize baked‐out and sintered nickel (Ni) electrode–Multilayer Ceramic Capacitors. The three‐dimensional microstructures obtained by two different tomography techniques were quantified and correlated. X‐ray nCT is sufficient to reveal the pore characteristics, whereas the FIB‐nT enables the particles in the initial packings to be identified. In the dielectric ceramic layers, pores preferentially orient horizontally in the layer and the regions near the Ni/BT interface are denser than the inner regions. This anisotropy is possibly caused by compressive stress induced during the heating stage.